Managing Evaluation of Training at Workplace - Khambayat, Rajesh P.; Khambayat, Shubhangi R. (Gyan Management Journal, 2017)
In today’s global economy, employees’ professional development through training is a vital element in any organization’s growth strategy. It is observed that in spite of good investment in training, many establishments do not always evaluate the impact of such training programmes. As in depth measurement of training effectiveness is costly. At the same time, considering the rise in training investment for employees, there is a growing need to evaluate training in a meaningful way, doing so can resultin a better allocation of training resources, cost savings, and increased productivity.Considering the significance of return on investment made for employee development, it is imperative to develop a system to help organizations in measurement of training effectiveness. An attempt is made in this paper to discuss the major challenges, including overall process and techniques associated with training evaluation. It will guide organizations in designing and conducting systematic training evaluation as well as for enhancing their competitiveness.